Short Communication: The correlation between foot circumference with the body length, shoulder height, and pelvic width in Sumatran elephants (Elephas maximus sumatranus) - HERY WIJAYANTO; DENY SETYO WIBOWO; RINI WIDAYANTI; TRI WAHYU PANGESTININGSIH; WORO DANUR WENDO; MACHMUD ASVAN; ANASTASIA STEPHANIE GUNAWAN; Marcel Wirabrata (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Wijayanto H, Wibowo DS, Widayanti R, Pangestiningsih TW, Wendo WD, Asvan M, Gunawan AS, Wirabrata M. 2021. Short Communication: The correlation between foot circumference with the body length, shoulder height, and pelvic width in Sumatran elephants (Elephas maximus sumatranus). Biodiversitas 22: 2635-2640. Sumatran elephants' body measurement is essential in conservation practices to perceive health status and determining medication doses. Considering elephants' size, the mahouts doing the recording can easily get harmed during their interaction with their animal. Therefore, easier method to shortening interaction time is urgently needed in estimating elephants' size. The aim of the research is to find out the correlations between forefoot and hindfoot circumference (FFC and HFC) with the body length (BL), shoulder height (SH), and pelvic width (PW) in Sumatran elephants. The correlation formula will very much reduce the time needed to measure the elephant size, since the mahouts only need to measure the foot circumference left by the elephant on the ground to predict BL, SH, and PW. The anatomical data were collected from adult elephants in Aceh, Safari Park Indonesia, Gembira Loka Zoo, Borobudur Park, and PLG Duri Pekanbaru. Measurements were done using modified Vernier calipers and roll meters, referring to standardized methods. The data then calculated using correlation and linear-regression test. From the results, we found that the FFC has very strong correlation with SH (R=0.809) and strong correlations with BL (R=0.769) and PW(R=0.73). Results from the HFC show very strong correlation with PW (R=0.826) and strong correlations with BL (R=0.775) and SH (R=0.747). In the conclusion, the foot circumference is very useful to predict the elephant's size and can much reduce the mahouts' risk by minimizing interaction time needed in elephant’s body measurement. For the field researcher, they are not necessary to meet with the elephants to predict the elephant’s size in the wild.